Restrictive Cardiomyopathy due to Secondary Haemochromatosis in a Beta Thalassaemia Major Patient: A Rare Entity - Kadir, ANM Monowarul; Afzal, Adrita; Mamun, Mohammad Al; Imam, Hasan; Qumruzzaman, Kh; Shameem, Md Kibriya; Salam, Md Abdus; Pasha, Mostofa Midhat; Hasan, Md Nazmul (University Heart Journal, 2025)
Haemochromatsis occurs due to iron over load. Thalassaemia major is an inherited disorder that can cause secondary haemochromatosis due to haemolysis and repeated blood transfusion. The secondary haemochromatosis in thalassaemia patient can rarely present with restrictive cardiomyopathy. Here, we report a case, where a 30-year-old woman with thalassaemia major presented with shortness of breath with paroxysmal nocturnal dyspnea, orthopnoea , oedema, skin pigmentation, raised Jugular venous pressure(JVP), cyanosis and bilateral basal crepitation. After through investigations, she was diagnosed as a case of heart failure due to restrictive cardiomyopathy with secondary haemochromatosis as a complication of repeated blood transfusion. She was treated with iron chelation therapy, furosemide, beta-blockers, angiotensin receptor blocker (ARB) and discharged with follow up. Iron chelation therapy should be imitated early to prevent secondary haemochromatsosis and its complications in thalassaemia major patient. University Heart Journal 2024; 20(2): 72-76